1993
DOI: 10.1152/jn.1993.70.5.1822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral vestibular stimulation on histamine release from the hypothalamus of rats in vivo

Abstract: 1. We investigated the effect of unilateral vestibular stimulation on histamine release from the anterior hypothalamic area of urethan-anesthetized rats in vivo, using a brain microdialysis method coupled with high-performance liquid chromatography fluorometry. 2. The histamine release was increased to approximately 180% of the basal release by the electrical stimulation of the inner ear with 1 Hz, 500 microA, and 200 ms for 20 min. This effect was dependent on the current intensity. 3. Activation of the unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…Unfortunately, there have been no studies where intracerebral administration of histamine receptor antagonists have been made into any of these nuclei during motion-induced emesis experimentation. However, it is thought that during provocative motion, a neural mismatch signal activates histaminergic neurons in the hypothalamus, and the histaminergic descending pathway to potentially stimulate H 1 receptors in the brainstem's “emetic center” (Takeda et al, 1986; Horii et al, 1993; Uno et al, 1997; Schmäl, 2013). Whilst the precise role of neuron and mast cell sources of histamine are not known, it is known that H 1 receptors are densely located in the NTS and DMNV, and also the vestibular nucleus; all areas are behind the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there have been no studies where intracerebral administration of histamine receptor antagonists have been made into any of these nuclei during motion-induced emesis experimentation. However, it is thought that during provocative motion, a neural mismatch signal activates histaminergic neurons in the hypothalamus, and the histaminergic descending pathway to potentially stimulate H 1 receptors in the brainstem's “emetic center” (Takeda et al, 1986; Horii et al, 1993; Uno et al, 1997; Schmäl, 2013). Whilst the precise role of neuron and mast cell sources of histamine are not known, it is known that H 1 receptors are densely located in the NTS and DMNV, and also the vestibular nucleus; all areas are behind the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of histamine on to the VN helps to explain the functional role of this neural loop activated when asymmetrical inputs reach the central vestibular structures (Horii et al, 1993). This loop could convey signals that promote the regulation of HDC gene expression leading to the release of histamine in the VN.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is highly implicated with the arousal level (Brown et al, 2001; Haas et al, 2008) and it has been shown that the horizontal vestibulo-ocular-reflex gain was very sensitive to the state of alertness (Flandrin et al, 1979; Matta and Enticott, 2004). Stimulation of the vestibular nerve enhances HA release in the hypothalamus and brainstem (Takeda et al, 1986; Horii et al, 1993, 1996; Uno et al, 1997). In vitro intracellular recordings from neurons in the medial and the lateral vestibular nuclei (VN; MVN and LVN) revealed HA induced depolarization via postsynaptic histamine H 1 (H 1 R; Inverarity et al, 1993) or H 2 receptors (H 2 R; Phelan et al, 1990; Serafin et al, 1993; Wang and Dutia, 1995; Zhang et al, 2008, 2013; Zhuang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is known to be released in the medulla and hypothalamus during the stress that accompanies vestibular dysfunction, such as in animal models of motion sickness (9) and after unilateral vestibular stimulation (10). Similarly, the histamine immunoreactivity in the vestibular nuclei is decreased following UL (5), thus indicating increased histamine release and depletion of central histamine stores.…”
Section: Discussionmentioning
confidence: 99%